Determinação de parâmetros para avaliação da estabilidade de taludes marginais em beira de rio - Bernál, Fernando Haetinger (2013)
Water is one of the major focuses of global debate on environmental sustainability, if not the foremost. The influence of water on natural systems and human life in general, and the continuity of its uses are increasingly conditioned, by the qualifications in management and the effectiveness of the measures that guarantee quality and quantity for the use of current and future generations. Among the concerns of any person or individual that plays a role in water resources management, the integrity of natural conditions is always desired. Maintaining the integrity of the natural conditions is a very complex process that takes into consideration geomorphological, climatic, biological and human aspects. Currently, there is no methodology available that allows one to determine with sufficient accuracy, from the analysis of multiple factors, the potential occurrence of falling marginal slopes in any stretch of the Jacuí River. The entire section of work on the Jacuí River is located in the Jacuí River basin, between kilometers 168 and 241, a total of 74 km. The objective of this study was to determine criteria for an integrated assessment of the marginal slope stability of the Jacuí River channel, stretching between the mouth of the Irapuá Creek and the Don Marco Dam, in the municipalities of Cachoeira do Sul and Rio Pardo, RS. The specific objectives were: identify and georeference the falling points of the marginal slopes of the studied section of the Jacuí River; identify criteria associated with the marginal slope instability; determine the integrity of variables that have a direct effect on the instability of slopes; identify critical locations of the falling sections of the marginal slopes in the studied stretch. Thus, knowing the specifics of the river requires understanding the processes in which one can determine the instability of the marginal slopes. The methodology consists of three phases: 1) a theoretical analysis of the possible factors that influence slope stability, 2) the preparation of the instrument used to capture survey data information, in the field and the existing base, to determine the marginal slope instability, and 3) search for interrelationship of the variables in the field, with the base map and the study of the association of these variables with the process of slope instability. Margins were classified according to a classification of falls (total amount of falls and their full length), of the bend of the river (Arrow), type of margin (constructive or destructive), and type of soil (Clay soil and Plan soil). The work concludes that it is possible to determine variables that explain the occurrence of falls, however there is no lone variable that explains the event. The declines stem from integrated processes that differ when it comes to falling sections and units. It was not possible to determine a standardized probability of falling, depending on the variability of interactions and the differentiation between the types of falls.